2016
DOI: 10.1182/blood-2016-01-635060
|View full text |Cite
|
Sign up to set email alerts
|

How I treat acute myeloid leukemia presenting with preexisting comorbidities

Abstract: Acute myeloid leukemia (AML) is a devastating disease with an incidence that progressively increases with advancing age. Currently, only ∼40% of younger and 10% of older adults are long-term survivors. If untreated, the overall prognosis of AML remains dismal. Initiation of therapy at diagnosis is usually urgent. Barriers to successful therapy for AML are the attendant toxicities directly related to chemotherapy or those associated with inevitable aplasia. Organ dysfunction often further complicates such toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 99 publications
1
26
0
1
Order By: Relevance
“…However, expert opinion suggests that non-anthracycline induction strategies should be considered where there is concern for tolerability of anthracycline-containing induction therapy. 95 Several anthracyclinefree intensive induction regimens have shown similar efficacy in comparison with "713" regimen, although only a minority was tested in randomized trials. [96][97][98][99][100] These options are listed in Table 6.…”
Section: Non-anthracycline Induction and Treatment Strategiesmentioning
confidence: 99%
“…However, expert opinion suggests that non-anthracycline induction strategies should be considered where there is concern for tolerability of anthracycline-containing induction therapy. 95 Several anthracyclinefree intensive induction regimens have shown similar efficacy in comparison with "713" regimen, although only a minority was tested in randomized trials. [96][97][98][99][100] These options are listed in Table 6.…”
Section: Non-anthracycline Induction and Treatment Strategiesmentioning
confidence: 99%
“…Despite rapid advances in AML therapy, including the development of novel drug targets and transplantation, treatment has remained stagnant for the past few decades, with most patients relapsing and dying of complications [16]. Even with current treatment, the majority of patients older than 65 years will die of AML within 1 year [17,18]. To address this issue, research has focused on the identification of novel targets for AML therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment choice also depends on a variety of factors, including age, performance status, and comorbidities (25). Studies have shown older patients with AML can benefit from standard therapy regimens; however, there is often reluctance among clinicians especially in the presence of comorbidities due to the difficulty of predicting risk/benefits of available therapies (11, 17, 26).…”
Section: Comorbidities and Amlmentioning
confidence: 99%